What is the underlying structure of the climate, conflict, and socio-economic system in Nigeria? A network analysis - Basel, Ashleigh Megan; Onivola Minoarivelo, Henintsoa; Craparo, Alessandro Carmelo William; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Nigeria, using network analysis. Results show that education and competition for resources are central elements in the underlying structure of Nigeria. Nutritional insecurities such as the number of malnourished and underweight children (node 8, 10) are connected to inequality and in turn conflict.